The Linkage of Social Maturity and School Well-Being in High School Students in Sidoarjo, Indonesia - Armando Jakarinda; Lely Ika Mariyati (Indonesian Journal of Cultural and Community Development, 2020)
This study is in the background by the existence of School Well-Being Problems in Vocational Students. This study aims to determine the relationship between Social Maturity and School Well-Being of Class X and XI Students in November 10, Sidoarjo Vocational High School. This research is a correlational quantitative study. This study uses a sample of 186 students consisting of classes X and XI. The sampling technique used is Statified Random Sampling. Data collection techniques in this study used 2 scales, the first was the social maturity scale and the School Well-Being scale. The results showed that the correlation coefficient was 0.993 with a significance level of p = 0.000 where p was smaller than 0.05. The results show that the hypothesis in this study is accepted. There is a relationship between social maturity with school well- being in class X and XI students in November 10, Sidoarjo Vocational High School.